Outcomes of Patients With Spinal Metastases From Prostate Cancer Treated With Conventionally-Fractionated External Beam Radiation Therapy. Issue 2 (March 2023) - Lee, Chia Ching; Tey, Jeremy; Cheo, Timothy; Lee, Chau Hung; Wong, Alvin; Kumar, Naresh; Vellayappan, Balamurugan
Study Design: Retrospective cohort study. Objective: To evaluate the outcomes of conventionally-fractionated external beam radiation therapy (cEBRT) in the treatment of prostate cancer spinal metastases (PCSM). Methods: Patients who received palliative cEBRT for PCSM in our institution between 2008 and 2018 were included. Our outcomes were local progression-free survival (LPFS), overall survival (OS), pain response and toxicities graded using CTCAE version 4.03. Univariable and multivariable Cox proportional hazard regressions were performed to identify predictors for LPFS and OS. Results: A total of 100 patients with 132 sites of PCSM were identified, with a median follow-up of 54 months. Fourteen-percent of patients underwent surgical intervention before receiving cEBRT. Eighteen spinal segments (13.6%) had local progression, with a median time to local progression of 8 months. The median LPFS and OS were 7.8 and 9.0 months, respectively. The complete and partial pain response rates were 57% and 39% respectively. The incidence of grade ≥3 acute toxicities was 11%. Better ECOG performance status (0 to 1), castration-sensitive disease, spinal surgery and use of novel antiandrogen agent were identified as significant predictors for improved OS on multivariable analysis. Conclusions: In our prostate cancer cohort, cEBRT is an effective treatment modality for local palliation of spinal metastases. More aggressive treatment approach should be considered for patients with excellent performance status and castration-sensitive disease in light of their expected longer survival. Further studies are warranted to identify the predictors for radiotherapy response in this population.